Insight into Potential Probiotic Markers Predicted in Lactobacillus pentosus MP-10 Genome Sequence - Abriouel, Hikmate; Pérez Montoro, Beatriz; Casimiro-Soriguer, Carlos S.; Pérez Pulido, Antonio J.; Knapp, Charles W.; Caballero Gómez, Natacha; Castillo-Gutiérrez, Sonia; Estudillo-Martínez, María D.; Gálvez, Antonio; Benomar, Nabil (Frontiers in Microbiology, 2017)
Lactobacillus pentosus MP-10 is a potential probiotic lactic acid bacterium (LAB) originally isolated from naturally fermented Aloreña green table olives. The entire genome sequence was annotated to in-silico analyze the molecular mechanisms involved in the adaptation of L. pentosus MP-10 to the human gastrointestinal tract (GIT), such as carbohydrate metabolism (related with prebiotic utilization) and the proteins involved in bacteria-host interactions. We predicted an arsenal of genes coding for carbohydrate-modifying enzymes to modify oligo- and polysaccharides, such as glycoside hydrolases, glycoside transferases and isomerases, and other enzymes involved in complex carbohydrate metabolism especially starch, raffinose and levan. These enzymes represent key indicators of the bacteria’s adaptation to the GIT environment, since they involve the metabolism and assimilation of complex carbohydrates not digested by human enzymes. We also detected key probiotic ligands (surface proteins, excreted or secreted proteins) involved in the adhesion to host cells such as adhesion to mucus, epithelial cells or extracellular matrix, and plasma components; also, moonlighting proteins or multifunctional proteins were found that could be involved in adhesion to epithelial cells and/or extracellular matrix proteins and also affect host immunomodulation. In-silico analysis of the genome sequence of L. pentosus MP-10 is an important initial step to screen for genes encoding for proteins that may provide probiotic features, and thus provides one new routes for screening and studying this potentially probiotic bacterium.